Răspuns :
Răspuns:
[(2 ÷ x - 17) × 3 - 15 ] ÷ 7 - 11 = 16
[( 2 ÷ x - 17) × 3 - 15 ] ÷ 7 = 16 + 11
[(2 ÷ x - 17) × 3 - 15 ] ÷ 7 = 27
[(2 ÷ x - 17) × 3 - 15] = 27 × 7
(2 ÷ x - 17) × 3 - 15 = 189
(2 ÷ x - 17) × 3 = 189 + 15
( 2 ÷ x - 17) × 3 = 204
2 ÷ x - 17 = 204 ÷ 3
2 ÷ x - 17 = 68
2 ÷ x = 68 + 17
2 ÷ x = 85
x = 2 / 85
/ = supra
SPER CA TE AM AJUTAT!
[(2:x-17)•3-15]:7=16+11
[(2:x-17)•3-15]:7=27
(2:x-17)•3-15=27•7
(2:x-17)•3-15=189
(2:x-17)•3=189+15
(2:x-17)•3=204
2:x-17=204:3
2:x-17=68
2:x=68+17
2:x=85
x=85•2
x=170
[(2:x-17)•3-15]:7=27
(2:x-17)•3-15=27•7
(2:x-17)•3-15=189
(2:x-17)•3=189+15
(2:x-17)•3=204
2:x-17=204:3
2:x-17=68
2:x=68+17
2:x=85
x=85•2
x=170